INFOGRAPHIC FOR PREGNANT WOMEN AND CAREGIVERS: EDUCATIONAL TECHNOLOGY IN THE CONTEXT OF OBSTETRIC CARE - Yany Suellen Pereira Cruz Oliveira; Roberta Costa; Margarete Maria de Lima; Manuela Beatriz Velho; Iris Elizabete Messa Gomes; Laís Antunes Wilhelm; Luana Pereira Ibiapina Coelho (Universidade Federal do Paraná, 2023)
Objective: to describe the process of construction and validation of an educational infographic with guidelines for pregnant women and companions in obstetric care in the context of Covid-19. Method: methodological research based on Instructional System Design guidelines and conducted from January 2021 to March 2022, in the State of Santa Catarina - Brazil, in three moments: scoping review, interviews with nurses from an Obstetric Emergency, and elaboration of educational technology and validation with experts. The analysis was anchored in content analysis with Content Validity Index. Results: the infographic addresses care for the prevention of Covid-19 infection, guidance on the onset of labor, when to seek maternity care, and care during hospitalization of pregnant women. The infographic obtained a Content Validity Index of 83.3%. Conclusion: educational technology was considered adequate for disseminating information and assisting professionals in promoting health and preventing injuries to the obstetric population.